Synthesis and Characterization of the New Manganese Hydroxide Chloride γ‐Mn(OH)Cl. Issue 42 (6th November 2018) - Falkowski, Viktoria; Zeugner, Alexander; Isaeva, Anna; Ruck, Michael; Huppertz, Hubert
Abstract : A new modification of Mn(OH)Cl was obtained under high‐pressure/high‐temperature conditions in a Walker‐type multianvil device. The pale pink, hygroscopic compound crystallizes in the orthorhombic space group Pnma (no. 62) with a = 602.90(4), b = 350.98(2), c = 1077.69(7) pm, and V = 228 × 10 6 pm 3 . The layered centrosymmetric structure consists of edge‐sharing Mn(OH)3 Cl3 octahedra arranged in sheets parallel to the (001) plane. The comparatively long H··· Cl distance of 275 pm suggests only weak hydrogen bonds between neighboring layers. Spin‐polarized scalar‐relativistic DFT+ U calculations predict a non‐conducting magnetically ordered ground state with a band gap of at least 3.2 eV and an effective magnetic moment of 4.65 µB /f. u. The experimentally determined magnetic response of Mn(OH)Cl is paramagnetic in the range of 10–300 K. The estimated moment of 5.6 µB /f. u. indicates the high‐spin d 5 configuration of manganese(II). We find hints for a long‐range magnetic ordering below 10 K. Abstract : The compound γ‐Mn(OH)Cl was synthesized under high‐pressure/high‐temperature conditions. Single‐crystal X‐ray diffraction reveals a layered structure composed of edge‐sharing fac ‐Mn(OH)3 Cl3 octahedra arranged in sheets. Characterization by magnetization experiments were complemented by spin‐polarized scalar‐relativistic DFT+ U calculations.